The Role Of National Education In The Formation Of Personal Spirituality - et. al., Ortiqova Dilbar Ortiqovna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article scientifically analyzes the role of national education in the formation of personality spirituality. The family is one of the oldest public organizations. The family lives according to centuries-old traditions, is a reliable foundation of a person, the core of his spirituality and morality. The family, in which a person spends most of his life, plays an extremely important role in society.